PENERAPAN KONVENSI JENEWA 1949 DAN PROTOKOL TAMBAHAN 1977 DALAM HUKUM NASIONAL INDONESIA (Studi tentang Urgensi dan Prosedur Ratifikasi Protokol Tambahan 1977) - ismail, isplancius (Faculty of Law, Universitas Jenderal Soedirman, 2013)
The Geneva Convention 1949 is an international treaty that regulates the victims of the international armed conflict and non-international armed conflict. The convention is supplemented by the Additional Protocol 1977 that governs the victims of international armed conflict (Additional Protocol I 1977) and victims of non-international armed conflict (Additional Protocol II 1977). Problems formulated in this study is how the implementation of these treaties in the Indonesian national law. The method used is normative juridical with secondary data and qualitative descriptive analysis. The results showed that the implementation of the Geneva Convention 1949 into Indonesia national law is done by Act No. 59 of 1958 on the Accession of the State of RI to the Geneva Conventions 1949. The urgency of Indonesia ratified the Additional Protocols of 1977 is in order that there will not have any doubts in practice. Wherease the practice of ratification in Indonesia is done by external and internal procedure.Â Key words : international treaty, armed conflict, accession, ratification